The Text Symmetry Approach in experience of Dr. Shogaa Al-Aani criticism التَّمَاثُلُ النَّصِيُ مُقارَبةٌ في تَجرِبَةِ الدّكتور شُجاع العَاني النَّقْدِيَّة - Khalid Ali Yaas خالد علي ياس (Journal Of Babylon Center For Humanities Studies, 2018)
This approachableness aims at scrutinizing the most important categories of intellectual which represented the Doctor Shuja' Al- 'Any's works and the extent to which he was influence by sociological criticism through out its different developmental phases ( stages ) starting from pre-modernism ( Reflection Theory ) passing by modernism up to post modernism ( socio – context criticism ) resulting in analytical knowledge for the literal – recital context necessarily led to generate patterning structuralism prevailing in these works which is clarified by what I have called ( context identicalness ) by juxtaposing of aesthetic - conversation between the internal structure ( recital components ) and the socio – cultural context and this is the main knowledge which the critic on in his all works. But the transition between these intellectual phases in criticism does not mean that the critic would leave any phase intellectually in a complete way when he moves to another , there is some sort of juxtaposition and interference all phases just as sociological mediator which is central in his critical writing ; where the transition to the context that is alluded by a certain sociological conception that suits the phase to which his thought belongs , which results in generating a wholistic suggestive structuralism which expresses all of these phases and works in a central vision as if it were one undivisible critical .